GLOBAL FINANCIAL CRISIS; RELATIONSHIP BETWEEN THE MORTGAGE LOAN RATES AND DOW JONES INDUSTRIAL AVERAGE STOCK INDEX AND THE IMPLICATION FOR THE NIGERIAN CAPITAL MARKET - Peter, Njiforti (European Scientific Journal, ESJ, 2012)
The convergence of global economy makes all countries and all markets sensible to the happening in other countries; the contagious effect is what makes other countries to take precautions against any impeding disaster. The recent global financial crisis that has its origin from USA has its way to affect the Nigerian Capital Market, this study employed econometric tools to establish the linkages between the mortgage loan rate, Dow Jones Industrial Average stock index and All Share Index, and it is established that the variables are not significantly related in such a way that the contagious effect will affect Nigerian Capital Market.